2022
DOI: 10.3390/children9121982
|View full text |Cite
|
Sign up to set email alerts
|

Gait Alterations in Two Young Siblings with Progressive Pseudorheumatoid Dysplasia

Abstract: Progressive pseudorheumatoid dysplasia (PPRD) is an autosomal recessive inherited skeletal dysplasia characterized by progressive non-inflammatory arthropathy affecting primarily the articular cartilage. Currently, little is known about the functional musculoskeletal aspects of these patients. In particular, an abnormal gait pattern has been described, without a clear hypothesis of the underlying causes in terms of muscular activity. This study presents the case of two siblings, 4 and 9 years old, a boy and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The role of the podiatrist (1), a healthcare profession that is often under-recognized, is crucial in the multidisciplinary approach to managing disabling conditions, particularly those of neurological origin in the pediatric population (2)(3)(4)(5)(6)(7). The importance of podiatry, as a subspecialty within orthopedics, becomes even more pronounced when dealing with young patients, where the emphasis should be on prevention as a primary intervention, in line with ethical principles (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the podiatrist (1), a healthcare profession that is often under-recognized, is crucial in the multidisciplinary approach to managing disabling conditions, particularly those of neurological origin in the pediatric population (2)(3)(4)(5)(6)(7). The importance of podiatry, as a subspecialty within orthopedics, becomes even more pronounced when dealing with young patients, where the emphasis should be on prevention as a primary intervention, in line with ethical principles (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…This special edition presents a variety of articles that further our understanding of novel assessments and interventions for improving gait and posture in the pediatric population. The special issue encompasses a case study [ 4 ], two case series [ 5 , 6 ], a prospective case-controlled study [ 7 ], and an updated meta-analysis [ 8 ], providing a comprehensive overview of the topic.…”
mentioning
confidence: 99%
“…In a case series by Sassi, Faccioli [ 5 ], the authors demonstrated the importance of novel gait and posture assessment strategies for determining appropriate rehabilitative interventions. The authors discussed two rare cases of Progressive Pseudohematoid Dysplasia in siblings manifesting gait abnormalities and muscle weakness.…”
mentioning
confidence: 99%